Wild Game: Further Processing of Wild Game Meat - Jason M. Scheffler; Chad Carr; Michael Fioretto; Jennifer G. Bearden; Halie Corbitt (EDIS)
This publication discusses further processing considerations for wild game meat, including foodborne illness concerns, meat storage, thawing, sausage making, and curing. Written by Jason M. Scheffler, Chad Carr, Michael Fioretto, Jennifer G. Bearden, and Halie Corbitt, and published by the UF/IFAS Department of Family, Youth and Community Sciences, May 2022.